Contamination of environmental objects with Eimeria spp. oocysts at the poultry farm - L. A. Bondarenko; R. R. Murzakov; R. T. Safiullin (Российский паразитологический журнал)
The scrapings taken inside the poultry house – floors and walls (28,2 % – Konstantinovskaia poultry and 34,8 % – PPV «Kuczynski») are the most contaminated with Eimeria spp. oocysts, the least – the territory near the poultry house. The maintenance of broilers in cages protects them from infection with Eimeria spp.